PENINGKATAN HASIL BELAJAR PKn MELALUI PEMBELAJARAN KOOPERATIF TIPE STUDENT TEAM ACHIEVEMENT DIVISION - Mendrofa, Harazaki (JURNAL PENA EDUKASI, 2018)
Abstract: This study is a classroom action research conducted in two cycles. Each cycle consists of two meetings and through four stages: planning, action, observation, and reflection. Subjects in this study were students of Class IV / A SD Negeri 070977 Gunungsitoli academic year 2016/2017 school year. Data collection techniques used are test and non-test techniques. Indicators of the success of this study include the percentage of student learning activities of at least 75%, the average grade of ≥75 with the percentage of classical learning completion of at least 75%, and the minimum teacher performance score of 71 (B). Based on the implementation of the first cycle the value of teacher performance was 83.08 (AB). In the second cycle, the value of teacher performance increased to 89.17 (A). Student learning activities reached 65.12% and in the second cycle increased to 79.87%. In cycle I, the average value of student learning outcomes reached 70.67 with the percentage of classical learning completion of 66.67%. Meanwhile, in the second cycle the average value of student learning outcomes increased to 81.67 with a percentage of classical learning completion of 93.33%. Based on the results of these studies it can be concluded that the application of STAD type cooperative learning models can improve teacher performance, student learning activities, and student learning outcomes. Keyword: Globalization, Student Team Achievment Division (STAD) Abstrak: Penelitian ini merupakan penelitian tindakan kelas yang dilaksanakan dalam dua siklus. Setiap siklus terdiri dari dua pertemuan dan melalui empat tahapan yaitu perencanaan, pelaksanaan tindakan, pengamatan, dan refleksi. Subjek dalam penelitian ini yaitu siswa Kelas IV/A SD Negeri 070977 Gunungsitoli Tahun ajaran 2016/2017.Teknik pengumpulan data yang digunakan yaitu teknik tes dan non tes. Indikator keberhasilan penelitian ini meliputi persentase aktivitas belajar siswa sekurang-kurangnya 75%, rata-rata nilai kelas ≥75 dengan persentase tuntas belajar klasikal sekurang-kurangnya 75%, dan nilai performansi guru minimal 71 (B). Berdasarkan pelaksanaan siklus I nilai performansi guru sebesar 83,08 (AB). Pada siklus II, nilai performansi guru meningkat menjadi 89,17 (A). Aktivitas belajar siswa mencapai 65,12% dan pada siklus II meningkat menjadi 79,87%. Pada siklus I, rata-rata nilai hasil belajar siswa mencapai 70,67 dengan persentase tuntas belajar klasikal sebesar 66,67%. Sementara itu, pada siklus II rata-rata nilai hasil belajar siswa meningkat menjadi 81,67 dengan persentase tuntas belajar klasikal sebesar 93,33%. Berdasarkan hasil penelitian tersebut dapat disimpulkan bahwa penerapan model pembelajaran kooperatif tipe STAD dapat meningkatkan performansi guru, aktivitas belajar siswa, dan hasil belajar siswa. Kata kunci: Globalisasi, Student Team Achievment Division (STAD)